From recreation mathematics to pseudo-genes - Noorbatcha, Ibrahim Ali; Shamsudin, Ahmad Faizul (IIUM Press, 2011)
An inspiration for life-like recreation could have come from a meta-magical theme proposed by Hofstadter (1986) that reproduces patterns of genies from "Lucas Tower", '"Towers of Hanoi" and "Towers of Brahma". Perhaps the phenomenon of meta-magics may unveil the mysteries of genes through new designs of gene structures unknown to nature. One day, it may help to solve the puzzles of human's mysterious diseases such as memory dysfunctions, cancer, AIDS, influenza viruses etc. This chapter is on the computer recreation of pseudo-genes using the modified mathematics of Towers of Hanoi. Pseudo-genes are not genes but are non-functional versions of genes. They may resemble other gene sequences and contain significant nucleotide substitutions, deletions and duplications. In combination with bio-molecular approach, this chapter will show how the computer generated pseudo-genes would have certain naturalness of brain disease related natural genes.